2022
DOI: 10.7150/ijbs.71581
|View full text |Cite
|
Sign up to set email alerts
|

PRMT5 acts as a tumor suppressor by inhibiting Wnt/β-catenin signaling in murine gastric tumorigenesis

Abstract: Previous studies have demonstrated the in vitro oncogenic role of protein arginine methyltransferase 5 (PRMT5) in gastric cancer cell lines. The in vivo function of PRMT5 in gastric tumorigenesis, however, is still unexplored. Here, we showed that Prmt5 deletion in mouse gastric epithelium resulted in spontaneous tumorigenesis in gastric antrum. All Prmt5-deficient mice displayed intestinal-type gastric cancer within 4 months of age. Of note, 20% (2/10) of Prmt5 mutants finally developed into invasive gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Unlike trimethylation on lysine, which usually presents the start of transcription process, the effect of dimethylation is more flexible, including both activation and suppression functions on different histones [ 42 ]. Therefore, the aberrant expression of PRMT5 leads to different results for different types of cells and the employment of PRMT5 inhibitors may have a selective effect [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike trimethylation on lysine, which usually presents the start of transcription process, the effect of dimethylation is more flexible, including both activation and suppression functions on different histones [ 42 ]. Therefore, the aberrant expression of PRMT5 leads to different results for different types of cells and the employment of PRMT5 inhibitors may have a selective effect [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gr1 + staining was quantified using Image J software. TUNEL staining was conducted through a TUNEL Assay Kit (#C10617, Invitrogen) 25 .…”
Section: Methodsmentioning
confidence: 99%
“…These PRMT family members can regulate the expression of tumor-associated genes, thereby promoting tumor cell proliferation, migration, and invasion. On the other hand, some studies have also found that the expression levels of PRMT2 and PRMT5 are down-regulated in tumors, and their functions are associated with inhibition of tumor cell proliferation and invasion [15,16]. This suggests that different PRMT family members may have different roles in tumors.…”
Section: Introductionmentioning
confidence: 99%